The Pirates of Penzance [videorecording (DVD)] - Michell, Keith; Oliver, Alexander (Tenor); Kelly, Janis, 1954-; Sullivan, Arthur, 1842-1900; Gilbert, W. S. (William Schwenck), 1836-1911 (Acorn Media, 2002)
Pirate apprentice Frederic becomes a pirate because of his sense of duty and he plans to go to the police and have his teachers arrested.